Tetanus in post-parturient cows - a report on six clinical cases - BHADWAL, M S; KUMAR, SUDARSHAN; WAZIR, V S; BHARDWAJ, H R; SHARMA, UTSAV (The Indian Journal of Animal Reproduction, 2023)
Six post-parturient cross-bred cows suffering from tetanus diagnosed based on history and clinic signs such as stiffness, lockjaw, erect ears etc; were treated with tetanus antitoxin, procaine pencillin G and diazepam. Five animals died of tetanus in spite of the treatment given. One animal survived the_ disease and was cured completely within two weeks time.
Keywords: Tetanus; post-parturient cows